2022
DOI: 10.1021/acssuschemeng.2c03428
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Insights into the Impacts of Calcite Nanoparticles on Methane Hydrate Formation

Abstract: Despite the potential broad utility of nanoparticles in hydrate-related fields, there remains a paucity of studies on the impacts of nanoparticles on gas hydrate formation. In this study, massive microsecond molecular dynamics simulations were performed to investigate the roles of calcite nanoparticles on the formation processes of methane hydrate. Our results indicate that calcite nanoparticles prefer to be in the water phase close to the water/gas interface. They inhibit methane hydrate nucleation because a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 86 publications
0
6
0
Order By: Relevance
“…The F 4φ is defined as F 4φ = ⟨cos­(3φ)⟩ with average values of −0.4, −0.04, and 0.7 for ice, liquid water, and hydrate, where φ is the torsion angle between two adjacent water molecules . The number of cages was analyzed by using the FSICA code, which can identify all the face-saturated hydrate cages associated with hydrate nucleation and growth. The growth rate of CO 2 hydrate was calculated as the rate of change of water molecules in the hydrate phase per unit cross-sectional area over time, similar to the procedure utilized in our previous works. , The sampling was performed over 50–150 ns. Ions incorporated in the hydrate phase were defined as those whose F 4φ of the first hydration shell (FHS) water was greater than 0.5.…”
Section: Methodsmentioning
confidence: 99%
“…The F 4φ is defined as F 4φ = ⟨cos­(3φ)⟩ with average values of −0.4, −0.04, and 0.7 for ice, liquid water, and hydrate, where φ is the torsion angle between two adjacent water molecules . The number of cages was analyzed by using the FSICA code, which can identify all the face-saturated hydrate cages associated with hydrate nucleation and growth. The growth rate of CO 2 hydrate was calculated as the rate of change of water molecules in the hydrate phase per unit cross-sectional area over time, similar to the procedure utilized in our previous works. , The sampling was performed over 50–150 ns. Ions incorporated in the hydrate phase were defined as those whose F 4φ of the first hydration shell (FHS) water was greater than 0.5.…”
Section: Methodsmentioning
confidence: 99%
“…Park and coworkers observed that CH 4 hydrate solids can stably intercalate within montmorillonite interlayers under conditions of lower pressure and higher temperature, suggesting that a portion of such clay mineral surface actively involved in promoting CH 4 hydrate formation . Recently, Ren et al reported that montmorillonite shortens the induction time of gas hydrate formation by providing additional nucleation sites but retards the growth kinetics of gas hydrate due to hindered mass transfer. , Several experimental studies have found that the phase equilibrium of CH 4 hydrate is inhibited in porous media composed of solid particles. Our previous study revealed that clay surfaces affect gas hydrate formation by changing the concentration of guest molecules and ions via the adsorption of water molecules, ions, and guest molecules. , On the other hand, the abundant organic matter in hydrate reservoirs will also affect the formation behavior of gas hydrates. , Liu and coworkers found that organic matter can kinetically promote gas hydrate formation by enhancing gas–water contact, and this effect was further enhanced by sulfur-containing acid-dissolvable organic matters. , Some studies revealed that organic matter molecules inhibit the formation of gas hydrates by association with water molecules. , It is worth noting that recent studies have observed that organic matter and clay minerals have a synergistic effect on the formation of gas hydrates, which significantly shortens the induction time for gas hydrate formation. Molecular dynamics (MD) simulations have been often employed to investigate the microscopic behavior of gas hydrates from the molecular scale. Based on MD simulation, some studies had reported that lignin, protein, humic acid, fatty acid, amino acid, and other organic matters , exhibit different effects on the formation and growth of gas hydrate. Furthermore, some MD simulation results found that clay mineral surfaces can repel organic matter or form organo-mineral complexes, significantly influencing the wettability of the clay surface. , The interaction between organic matter and clay surfaces complicates the formation processes of gas hydrates.…”
Section: Introductionmentioning
confidence: 99%
“…22,23 Calcite nanoparticles in the aqueous phase are close to the water/air interface, and a layer of bound water is formed around each nanoparticle, thereby inhibiting the nucleation of methane hydrate. 24 The fundamental process underlying hydrate formation involves the rearrangement of water molecules under specific conditions as they transform into hydrates. To gain insights into how nanoparticles affect hydrate formation, it is necessary to investigate their impact on the water molecule arrangement.…”
Section: Introductionmentioning
confidence: 99%